1990
DOI: 10.2176/nmc.30.610
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage Associated with Nontraumatic Disseminated Intravascular Coagulation

Abstract: The authors report four cases of intracranial hemorrhage associated with nontraumatic disseminated intravascular coagulation (DIC). Two cases demonstrated a sudden onset of intracerebral hemorrhage. The other two showed chronic subdural hematoma initially, followed by acute multiple intracranial hemorrhages or general hemorrhagic diathesis. The underlying disorders were glioblastoma multiforme, thoracoabdominal aortic aneurysm, acute promyelocytic leukemia, and stomach cancer associated with disseminated carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Age, systemic complications such as cardiovascular disease in elderly patients, coagulopathy, and poor preoperative neurological state are contributory causes of postoperative death. 7,15,21,35) In the present study, 50% of deaths were due to DIC. Statistical analysis also showed that coagulation disturbance was significantly correlated to poor outcome.…”
Section: Discussionsupporting
confidence: 45%
“…Age, systemic complications such as cardiovascular disease in elderly patients, coagulopathy, and poor preoperative neurological state are contributory causes of postoperative death. 7,15,21,35) In the present study, 50% of deaths were due to DIC. Statistical analysis also showed that coagulation disturbance was significantly correlated to poor outcome.…”
Section: Discussionsupporting
confidence: 45%
“…20,23,[39][40][41][42][43] In contrast to the improvement in survival and decrease of hemorrhagic complications resulting from the introduction of ATRA, changes in hemorrhagic mortality have been reported to be minimal. 10 In our study, FICH was not decreased after ATRA use (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…But, there are other causes such as autoregulatory dysfunction with excessive cerebral blood flow (e.g., reperfusion injury, hemorrhagic transformation, cold exposure), rupture of an aneurysm or arteriovenous malformation and altered hemostasis (e.g., thrombolysis, anticoagulation, bleeding diathesis). [5] In our case, widespread thrombin generation and clotting results in coagulopathies and bleeding tendency from depletion of coagulation factors, platelets and secondary fibrinolysis with resultant hemorrhage. [13] ICH associated with non-traumatic DIC is often accompanied by encephalopathy.…”
Section: Discussionmentioning
confidence: 71%
“…[11] ICH associated with DIC has been reported in non-sepsis patients. [4,5,15,16] Radiological findings of subdural hematoma, subarachnoid and massive lobar hemorrhages, and hemorrhagic infarcts (often in association with venous sinus thrombosis), have been occasionally described. [5,[15][16][17] However, reports on ICH associated with DIC caused by sepsis are rare in English-language literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation